INITIAL STEP OF ASSESSING THE EFFECTS OF DEXILANT 60MG TREATMENT IN PATIENTS WITH GERD WITH ESOPHAGEAL INJURY AF¬TER 4 WEEK OF TREATMENT - Nguyễn Chí , Tùng; Nguyễn Thái , Sơn; Nguyễn Văn , Chương (Journal of 175 Practical Medicine and Pharmacy, 2024)
Objective: to evaluate the effectiveness of Dexilant treatment in GERD patients with esophageal lesions. Subjects and Methods: This is a descriptive prospective study. We conducted a study on 39 cases of GERD with esophageal lesions. Results: After treatment, most of the clinical symptoms decreased significantly, p<0.05. The rate of reduction of clinical symptoms was statistically significant, p<0.05. With a reduction rate ranging from 88.3% - 100%, in which the typical symptoms of GERD are heartburn, regurgitation is the most effective with the rate of 97% and 100%, respectively. Change in frequency of GerdQ questions after treatment in a positive direction has statistical significance, p<0.05. The degree of reduction of clinical symptoms according to the GerdQ scale before and after treatment was statistically significant, p<0.0001. The rate of reduction in the level of GerdQ score 11-18 after treatment was the highest with 100%; level of 8-10 points, down 95.2%. There were 97.4% of the study subjects switched to the level of 3-7 points. - After treatment, the rate of healing of esophageal lesions decreased significantly, p<0.0001. 100% of patients with Grade B esophageal lesions recovered after treatment. 28/31 (90.3%) of patients with Grade A esophageal lesions were healed after treatment. Only 7.7% of patients have not yet healed. However, the extent of damage is also significantly reduced. No adverse effects of the drug have been reported. Conclusion: Dexilant has a very good therapeutic effect on GERD patients with esophageal lesions.